Factors Associated with Stroke Incidence at Advent Hospital Bandar Lampung - Anisa, Irma (Genius Journal, 2025)
Introduction: Stroke is a serious neurovascular condition caused by impaired cerebral blood flow, resulting in neurological deficits and potentially permanent disability or death. Modifiable risk factors such as body mass index (BMI), diabetes mellitus, and hypertension have been shown to significantly influence stroke incidence. Objective: This study aimed to analyze the relationship between BMI, blood glucose levels, and hypertension with stroke incidence at Adventist Hospital Bandar Lampung. Method: A quantitative, cross-sectional study design was used, involving stroke patients selected through simple random sampling. Data were collected through medical record review and analyzed using the Chi-square test with a predetermined level of significance. Results: The findings revealed significant associations between BMI, diabetes status, and hypertension with stroke type. Individuals with normal BMI were more likely to experience non-hemorrhagic stroke, while those with abnormal BMI had a higher tendency toward hemorrhagic stroke. Patients with elevated blood glucose levels were more frequently diagnosed with non-hemorrhagic stroke. Similarly, individuals with hypertension showed a stronger tendency toward non-hemorrhagic stroke compared to those with normal blood pressure. Conclusion: BMI, blood glucose levels, and hypertension are significantly related to the type and occurrence of stroke. These results underline the importance of maintaining a healthy lifestyle by regulating weight, managing blood sugar, and controlling blood pressure. Strengthening health education and preventive strategies through hospital-based media can help reduce stroke risk. Further research is encouraged to explore other contributing factors and to enhance clinical practices in stroke prevention and management.